Quetiapine and rivastigmine and cognitive decline in Alzheimer's disease: randomised double blind placebo controlled trial. Issue 7496 (18th February 2005) - Ballard, Clive; Margallo-Lana, Marisa; Juszczak, Edmund; Douglas, Simon; Swann, Alan; Thomas, Alan; O'Brien, John; Everratt, Anna; Sadler, Stuart; Maddison, Clare; Lee, Lesley; Bannister, Carol; et al.
Abstract: Objectives To determine the respective efficacy of quetiapine and rivastigmine for agitation in people with dementia in institutional care and to evaluate these treatments with respect to change in cognitive performance. Design Randomised double blind (clinician, patient, outcomes assessor) placebo controlled trial. Setting Care facilities in the north east of England. Participants 93 patients with Alzheimer's disease, dementia, and clinically significant agitation. Intervention Atypical antipsychotic (quetiapine), cholinesterase inhibitor (rivastigmine), or placebo (double dummy). Main outcome measures Agitation (Cohen-Mansfield agitation inventory) and cognition (severe impairment battery) at baseline and at six weeks and 26 weeks. The primary outcome was agitation inventory at six weeks. Results 31 patients were randomised to each group, and 80 (86%) started treatment (25 rivastigmine, 26 quetiapine, 29 placebo), of whom 71 (89%) tolerated the maximum protocol dose (22 rivastigmine, 23 quetiapine, 26 placebo). Compared with placebo, neither group showed significant differences in improvement on the agitation inventory either at six weeks or 26 weeks. Fifty six patients scored > 10 on the severe impairment battery at baseline, 46 (82%) of whom were included in the analysis at six week follow up (14 rivastigmine, 14 quetiapine, 18 placebo). For quetiapine the change in severe impairment battery score from baseline was estimated as an average of -14.6 points (95% confidence interval -25.3 to -4.0) lower (that is, worse) than in the placebo group at six weeks (P = 0.009) and -15.4 points (-27.0 to -3.8) lower at 26 weeks (P = 0.01). The corresponding changes with rivastigmine were -3.5 points (-13.1 to 6.2) lower at six weeks (P = 0.5) and -7.5 points (-21.0 to 6.0) lower at 26 weeks (P = 0.3). Conclusions Neither quetiapine nor rivastigmine are effective in the treatment of agitation in people with dementia in institutional care. Compared with placebo, quetiapine is associated with significantly greater cognitive decline.